2020
DOI: 10.1097/mnh.0000000000000645
|View full text |Cite
|
Sign up to set email alerts
|

Current and novel imaging techniques to evaluate myocardial dysfunction during hemodialysis

Abstract: Purpose of review Patients on hemodialysis have significantly higher rates of cardiovascular mortality resulting from a multitude of myocardial dysfunctions. Current imaging modalities allow independent assessment of cardiac morphology, contractile function, coronary arteries and cardiac perfusion. Techniques such as cardiac computed tomography (CT) imaging have been available for some time, but have not yet had widespread adoption because of technical limitations related to cardiac motion, radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Initial PET-based study findings have been supported by further human intradialytic imaging studies. High-resolution computed tomography–based (with spatial resolution down to 3 mm) 71 and arterial spin labeled intradialytic cardiac MRI have revealed identical findings. 48 In addition, these studies have confirmed the linear relationship of ultrafiltration rate to the severity of hemodialysis-induced myocardial stunning (as assessed with tagged cardiac MRI and the number of new areas of segmental loss of contractile function regional wall motion abnormalities) 48 and that changes in myocardial perfusion are not associated with paired changes in larger coronary arterial blood flow.…”
Section: Heartmentioning
confidence: 86%
“…Initial PET-based study findings have been supported by further human intradialytic imaging studies. High-resolution computed tomography–based (with spatial resolution down to 3 mm) 71 and arterial spin labeled intradialytic cardiac MRI have revealed identical findings. 48 In addition, these studies have confirmed the linear relationship of ultrafiltration rate to the severity of hemodialysis-induced myocardial stunning (as assessed with tagged cardiac MRI and the number of new areas of segmental loss of contractile function regional wall motion abnormalities) 48 and that changes in myocardial perfusion are not associated with paired changes in larger coronary arterial blood flow.…”
Section: Heartmentioning
confidence: 86%
“…Among them, the most validated are the changes in echography assessment of left ventricle mass [ 46 ] or doppler estimation of arterial stiffness via pulse wave velocity [ 47 ]. A more recent technique (dynamic contrast-enhanced CT imaging) can be used to acquire high-resolution cardiac images and provide an accurate estimation of cardiac perfusion [ 48 ]. Moreover, regional and national study registry might improve and standardize the long-term follow-up of chronic HD patients reporting adverse events and causes of death using MCO.…”
Section: From Delphi Approach To the Real Life In Dialysis Units: Des...mentioning
confidence: 99%